Bedside ultrasound education in Canadian medical schools: A national survey - Steinmetz, Peter; Dobrescu, Octavian; Oleskevich, Sharon; Lewis, John (Canadian Medical Education Journal, 2016)
Background: This study was carried out to determine the extent and characteristics of bedside ultrasound teaching in medical schools across Canada. Methods: A cross-sectional, survey-based study was used to assess undergraduate bedside ultrasound education in the 17 accredited medical schools in Canada. The survey, consisting of 19 questions was pilot-tested, web-based, and completed over a period of seven months in 2014. Results: Approximately half of the 13 responding medical schools had integrated bedside ultrasound teaching into their undergraduate curriculum. The most common trends in undergraduate ultrasound teaching related to duration (1-5 hours/year in 50% of schools), format (practical and theoretical in 67% of schools), and logistics (1:4 instructor to student ratio in 67% of schools). The majority of responding vice-deans indicated that bedside ultrasound education should be integrated into the medical school curriculum (77%), and cited a lack of ultrasound machines and infrastructure as barriers to integration. Conclusions: This study documents the current characteristics of undergraduate ultrasound education in Canada.